Pengembangan Chem-Magz Berbasis Flipbook Maker sebagai Sumber Belajar Mandiri Peserta Didik Kelas XI MIPA - Algiffary, Khaliq; Aulia, Army; Husain, Halimah (Chemistry Education Review (CER), 2022)
This study aims to describe the profile of Chem-Magz colloid system based on Flipbook Maker as a learning resource for high school students and produce a colloidal system Chem-Magz product based on Flipbook Maker as a valid, practical, and effective learning resource for high school students. The type of research used in this research is development research or R&D with the ADDIE development model. This research was conducted at SMA Negeri 1 Kalukku in class XI MIPA students. The data collection technique uses an instrument in the form of a product assessment questionnaire to assess aspects of validity, assess aspects of practicality, and to assess aspects of the effectiveness of learning media. The results of the study show that the development profile of Chem-Magz based on flipbook maker consists of 1) Cover or cover designed using Adobe InDesign with a background image related to colloidal material 2) Supporting Information related to brief information about Chem-Magz 3) Contents or table of contents according to sub main subject of colloid system 4) Content of material consisting of colloid system material which is equipped with supporting images and videos 5) The tasks listed in the design are as attractive as possible and 6) Cover Cover with background images related to the material and contains a cover about colloid system material and in general, the results of the flipbook maker-based Chem-Magz development in this study are valid, practical and effective. (a) Valid, based on the results of validation by experts at Chem-Magz based on flipbook maker obtaining an average score of 3.76 with a very valid category which lies in the range of 3.5 X/Y/Z 4 with a very valid category, (b) practical, based on observations by observers that the learning device was "completely implemented" during the trial with an average value of 1.96 which was in the range of 1.5 M 2.0, while the overall response of teachers and students was in the category of "Very Positive" and (c) effective, the classical completeness of student learning outcomes is achieved which shows that the percentage of student learning outcomes of 40% is in the very good category, 48% is in the good category, 4% is in the sufficient category, and 8% in the less category. Table 4.12 shows that of the 25 students who took the learning outcomes test, there were 90% who achieved classical completeness, namely 23 students who completed and 10% who did not achieve classical completeness, namely 2 students who did not complete.